An Investigation on the Factor of Media Consumption to Civic Engagement and Political Participation: Examining the Impact of Media Consumption on Civic Engagement and Political Participation (Journal of Advances and Scholarly Researches in Allied Education, 2012)
A national UK survey (N = 1017) examined the associationbetween media consumption and three indicators of civic participation –likelihood of voting, interest in politics, and actions taken in response to apublic issue of concern to the respondent. Multiple regression analysis wasused to test the variance explained by media use variables after firstcontrolling for demographic, social and political predictors of each indicatorof participation. Media use significantly added to explaining variance in civicparticipation as follows. In accounting for voting, demographic andpolitical/social factors mattered, but so too did some media habits (listeningto the radio and engagement with the news). Interest in politics was accountedfor by political/social factors and by media use, especially higher newsengagement and lower media trust. However, taking action on an issue of concernwas accounted for only by political/social factors, with the exception thatslightly fewer actions were taken by those who watched more television. Thesefindings provided little support for the media malaise thesis, and instead wereinterpreted as providing qualified support for the cognitive/motivationaltheory of news as a means of engaging the public.